2005
DOI: 10.1088/0741-3335/47/12b/s48
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure microwave torch for synthesis of carbon nanotubes

Abstract: The microwave (mw) plasma torch at atmospheric pressure has been studied for carbon nanotube (CNT) synthesis. The depositions were carried out on silicon substrates with 5-15 nm thin iron catalytic overlayers from the mixture of argon, hydrogen and methane. The optical emission spectroscopy of the torch showed the presence of C 2 and CH radicals as well as carbon and hydrogen excited atoms. The vicinity of the substrate influenced the relative intensities and increased the emission of C 2 . For fixed mw power,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Therefore, it also resulted in bulk production of unaligned CNTs [37,38]. However, we have shown that MW torch is capable of the high-speed synthesis of vertically aligned supported CNTs [39][40][41]. This paper provides a critical overview of the previous experiments, supplemented by recent improvements of the torch design and deposition procedure, discharge diagnostics, the study of catalyst phase, and effects of underlaying material.…”
Section: Chemical Vapor Deposition Of Carbon Nanotubesmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, it also resulted in bulk production of unaligned CNTs [37,38]. However, we have shown that MW torch is capable of the high-speed synthesis of vertically aligned supported CNTs [39][40][41]. This paper provides a critical overview of the previous experiments, supplemented by recent improvements of the torch design and deposition procedure, discharge diagnostics, the study of catalyst phase, and effects of underlaying material.…”
Section: Chemical Vapor Deposition Of Carbon Nanotubesmentioning
confidence: 98%
“…Ferrite circulator protected the generator from the reflected power by re-routing it to the water load. Matching of the plasma load to the line impedance was achieved by a combination of a movable short plunger and a line stretcher as described in [39]. The coaxial line and the nozzle electrode accommodated a dual gas flow.…”
Section: Design Of Mw Torch and Its Present Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments with microwave (mw) torches are focused on the floating catalyst approach (ferrocene, iron pentacarbonyl), ie , also bulk production of unaligned CNTs [10]. On the other hand, the mw torch has been successfully used by our group for high speed synthesis of vertically aligned supported CNTs [11][12]. With regard the dielectric barrier discharges (DBDs), Kyung, Lee et al .…”
Section: Carbon Nanotubes Synthesis By Pecvd At Atmospheric Pressurementioning
confidence: 99%
“…The temperature of the substrate is measured by Raytek Thermalert TX pyrometer from its backside. More details of the microwave torch construction are given in [5].…”
Section: Description Of the Reactor For Cnt Depositionmentioning
confidence: 99%